2021
DOI: 10.1038/s41598-021-91350-9
|View full text |Cite
|
Sign up to set email alerts
|

The entropy of chaotic transitions of EEG phase growth in bipolar disorder with lithium carbonate

Abstract: The application of chaos measures the association of EEG signals which allows for differentiating pre and post-medicated epochs for bipolar patients. We propose a new approach on chaos necessary for proof of EEG metastability. Shannon entropies of concealed patterns of Schwarzian derivatives from absolute instantaneous frequency transformations of EEG signals after Hilbert transform are compared and found significantly statistically different between pre and post-medication periods when fitted to von Bertalanf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…We show that lithium inhibits chaotic phase transitions 11 . We showed that the energy change that occurs during chaotic phase transitions divides the bipolar disorder spectrum into three subgroups 12 .…”
Section: Dıscussıonmentioning
confidence: 78%
“…We show that lithium inhibits chaotic phase transitions 11 . We showed that the energy change that occurs during chaotic phase transitions divides the bipolar disorder spectrum into three subgroups 12 .…”
Section: Dıscussıonmentioning
confidence: 78%
“…The aim of giving a uniform treatment was to standardize the prophylactic treatment. Whilst lithium normalizes beta, delta, and theta activities, treatment response is most closely associated with basal delta activity ( 31 , 32 ). In light of our findings, the association between the delta activities of healthy first-degree relatives and bipolar patients in ongoing remission with lithium, diverting from unrelated healthy controls, seems meaningful in this aspect.…”
Section: Discussionmentioning
confidence: 99%
“… 49 , 50 , 51 , 52 , 53 In particular, TE has also been employed to analyse electroencephalogram signals in individuals with mood disorders. 54 , 55 , 56 …”
Section: Introductionmentioning
confidence: 99%